Response to Comment on "Eppur si Muove: Proton Diffusion in Halide Perovskite Single Crystals": Measure What is Measurable, and Make Measurable What is Not So: Discrepancies between Proton Diffusion in Halide Perovskite Single Crystals and Thin Films. Issue 35 (26th July 2021) - Ceratti, Davide Raffaele; Zohar, Arava; Hodes, Gary; Cahen, David
Abstract: Buffeteau et al. note that the proton diffusion coefficient in MAPbI3 that is deduced (by the authors) from results, obtained by a suite of complementary techniques, on a large number of single crystals ( Adv. Mater . 2020, 32, 2002467) is 5 orders of magnitude higher than what is estimated (by them) in J. Am. Chem. So c . 2020, 142, 10431, from infrared spectroscopy on ultrathin MAPbI3 films; use of (deuterium/hydrogen) D/H isotope substitution is common to both studies. Buffeteau et al. speculated that proton diffusion in halide perovskite single crystals is dominated by 1D defects, which will somehow not be present in thin films, as those are made up of small‐sized crystallites. It is shown here that the idea of a 1D defect is not supported by the body of experimental data gathered on these crystals, that the statistical analysis employed in to Buffeteau et al. to support the criticism is problematic, and it is concluded that the source of the difference must lie elsewhere. Constructive suggestions for this difference are provided and experiments to discern between possible reasons for it are proposed. Abstract : What can explain the 10 5 times difference higher value of the proton diffusion coefficient in iodide perovskite single crystals relative to other reported values in thin films? Instead of migration through imperfections, which is shown to be highly improbable, experimentally testable alternatives are proposed.